Scenario Forecasting of Agriculture Institutional Transformation on Sustainable Development Base - Liubov, Vodianka; Antochova, Irina; Kobelia, Zoriana; Антохов, Андрій; Podluzhna, Natalia; SAICHUK, VIKTOR (My University, 2021)
This article examines the correlation between the increase in age groups of population and branch structure of employment in the Ukrainian economy. Today, the study of human capital's impact on economic processes is an essential economic science component. The application of quantitative methods in this relationship's study provides essential information about the nature of the interconnection of individual characteristics of human capital and critical socio-economic processes in the current domestic economic reality. Applying correlation-regression analysis, modelling these interdependencies with multiple regression models, and estimating corre-lation and deterministic relationships, in particular, are essential means in the practical study of this macroeco-nomic resource impact. Economic and mathematical analysis of the interdependencies between employment in agricultural, industrial, and financial sectors and the growth of the Ukrainian population's age groups were carried out. Based on these data, conclusions were drawn about critical macroeconomic processes, which are quantitatively confirmed by the built models. The role of the age structure of the population in structural trans-formations of the Ukrainian economy was evaluated.
Keywords: Correlation-regression analysis; human capital; econometric model; economic and demographic processes